Wake of a shattering fuel drop - Girin, O.G. (Reports of the National Academy of Sciences of Ukraine, 2015)
A mathematical model, which describes the evaporation ballistics of a mist in the wake of a shattering drop, is elaborated. The stripped droplets are considered as a multivelocity continuum, and a system of equations describing the two-phase polydisperse spray dynamics is proposed. The problem is formulated in a one-dimensional spatial approximation of the flowfield and is solved in closed form in a dynamic 3D space. This study includes a detailed calculation of the ballistics of an evaporating spray generated in the wake of a kerosene drop fragmented by an air stream. The structure of the spray related to the dynamic process of spray formation, the evolution of the dispersive characteristics of the liquid-phase spray jet, the stabilization and the range of a jet, and the vapor cloud formation are investigated.